Sleep, short-term memory, and mood states of volunteers with increasing altitude - Wang, Huanhuan; Li, Xueyan; Li, Jianhua; Gao, Yinghui; Li, Weihua; Zhao, Xinke; Wen, Ruoqing; Han, Jiming; Chen, Kaibing; Liu, Lin (Frontiers in Psychiatry, 2022)
Purpose This study sought to identify the changes and potential association between sleep characteristics and short-term memory, and mood states among volunteers at different altitudes and times. Method A total of 26 healthy volunteers were recruited from the PLA General Hospital, and we conducted a longitudinal prospective survey for over 1 year from November 2019 to April 2021. First, we collected demographic data, sleep parameters by overnight polysomnography (PSG), short-term memory by digit span test, and mood states by completing a questionnaire with a brief profile of mood states among participants in the plain (53 m). Then, we continuously followed them up to collect data in the 3rd month at an altitude of 1,650 m (on the 3rd month of the 1-year survey period), the 3rd month at an altitude of 4,000 m (on the 6th month of the 1-year survey period), and the 9th month at an altitude of 4,000 m (on the 12th month of the 1-year survey period). Multiple linear regression analysis was used to construct models between sleep parameters and short-term memory, and mood states. Results The prevalence of sleep apnea syndrome (SAS) significantly increased with rising elevation (P < 0.01). The apnea-hypopnea index (AHI), the mean apnea time (MAT), the longest apnea time (LAT), and the duration of time with SaO2 < 90% (TSA90) were increased (P < 0.05), and the mean pulse oxygen saturation (MSpO2), the lowest pulse oxygen saturation (LSpO2), and heart rate were significantly decreased with increasing altitude (P < 0.05). Digit span scores were decreased with increasing altitude (P < 0.001). A negative mood was more severe and a positive mood increasingly faded with rising elevation (P < 0.001). Additionally, linear correlation analysis showed that higher AHI, LAT, and MAT were strongly associated with a greater decline in short-term memory (in the 3rd and 9th month at an altitude of 4,000 m, respectively: rs = −0.897, −0.901; rs = −0.691, −0.749; rs = −0.732, −0.794, P < 0.001), and also were strongly associated with more severe negative mood (in the 3rd month at altitudes of 1,650 m and 4,000 m, respectively: rs = 0.655, 0.715, 0.724; rs = 0.771, 0.638, 0.737, P < 0.000625). Multiple linear regression pointed out that AHI was a significant predictor of negative mood among people at different altitudes (in the 3rd month at an altitude of 1,650 m: TMD = 33.161 + 6.495*AHI; in the 3rd month at an altitude of 4,000 m: TMD = 74.247 + 1.589*AHI, P < 0.05). Conclusion SAS developed easily in high altitudes, most often in CSA (central sleep apnea, CSA). The sleep, short-term memory, and negative mood were significantly more damaged with elevation in volunteers. Sleep parameters were closely associated with short-term memory and mood states in volunteers at high altitudes; the higher the sleep parameters (AHI, LAT, and MAT) scores, the more significant the mood disorders and the more obvious impairment of short-term memory. AHI was a critical predictor of the negative mood of volunteers at different altitudes. This study provides evidence that could help with the prevention and control of sleep disorder, cognitive disorder, and negative mood among populations with high altitudes.